"Not One of Us": Predictors and Consequences of Denying Ingroup Characteristics to Ambiguous Targets. (October 2014) - Kteily, Nour; Cotterill, Sarah; Sidanius, Jim; Sheehy-Skeffington, Jennifer; Bergh, Robin
We investigated individual difference predictors of ascribing ingroup characteristics to negative and positive ambiguous targets. Studies 1 and 2 investigated events involving negative targets whose status as racial (Tsarnaev brothers) or national (Woolwich attackers) ingroup members remained ambiguous. Immediately following the attacks, we presented White Americans and British individuals with the suspects' images. Those higher in social dominance orientation (SDO) and right-wing authoritarianism (RWA)—concerned with enforcing status boundaries and adherence to ingroup norms, respectively—perceived these low status and low conformity suspects as looking less White and less British, thus denying them ingroup characteristics. Perceiving suspects in more exclusionary terms increased support for treating them harshly, and for militaristic counter-terrorism policies prioritizing ingroup safety over outgroup harm. Studies 3 and 4 experimentally manipulated a racially ambiguous target's status and conformity. Results suggested that target status and conformity critically influence SDO's (status) and RWA's (conformity) effects on inclusionary versus exclusionary perceptions.